UiTM host delegation from Namangan Institute of Engineering and Technology, Uzbekistan in efforts to strengthen global ties / Norkasihan Ibrahim and Gurmeet Kaur Surindar Singh - Ibrahim, Norkasihan; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2023)
On November 15th, 2023, the Faculty of Pharmacy UiTM graciously welcomed distinguished delegates from Namangan Institute of Engineering and Technology, Uzbekistan, to the UiTM Puncak Alam Campus. This visit represents a significant opportunity to bolster UiTM's global standing and performance. Professor Ergashev Oybek, ViceRector of Scientific Affairs and Innovations, led the Namagan Institute delegates along with four faculty members and seven students.